2017
DOI: 10.1007/s00221-017-4962-z
|View full text |Cite
|
Sign up to set email alerts
|

Nigral injection of a proteasomal inhibitor, lactacystin, induces widespread glial cell activation and shows various phenotypes of Parkinson’s disease in young and adult mouse

Abstract: Proteinaceous inclusions, called Lewy bodies, are used as a pathological hallmark for Parkinson's disease (PD). Lewy bodies contain insoluble α-synuclein (aSyn) and many other ubiquitinated proteins, suggesting a role for protein degradation system failure in the PD pathogenesis. Indeed, proteasomal dysfunction has been linked to PD but commonly used in vivo toxin models, such as 6-OHDA or MPTP, do not have a significant effect on the proteasomal system or protein aggregation. Therefore, we wanted to study the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 60 publications
4
14
0
Order By: Relevance
“…Previous reports have shown an increased ipsilateral SNr α-syn immunoreactivity to lactacystintreatment in both mice and rats compared to control animals accompanied by neuroinflammation and oxidative stress (Miwa et al, 2005;Savolainen et al, 2017). We observed immunopositive α-syn granules in both the ipsilateral and contralateral SNr that were slightly more pronounced in the lactacystin-than the saline-injected animals (Figure 7), presumably caused by the minor inflammatory response seen in these animals.…”
Section: Discussionsupporting
confidence: 51%
“…Previous reports have shown an increased ipsilateral SNr α-syn immunoreactivity to lactacystintreatment in both mice and rats compared to control animals accompanied by neuroinflammation and oxidative stress (Miwa et al, 2005;Savolainen et al, 2017). We observed immunopositive α-syn granules in both the ipsilateral and contralateral SNr that were slightly more pronounced in the lactacystin-than the saline-injected animals (Figure 7), presumably caused by the minor inflammatory response seen in these animals.…”
Section: Discussionsupporting
confidence: 51%
“…Loss of dopaminergic neurons has been reported with impaired motor behavior and filamental proteinaceous inclusions in brain regions affected by PD. However, later studies could not reproduce most of these findings, although some aspects of the model, such as the loss of nigral dopaminergic neurons and accumulation of proteinaceous inclusions, have been replicated (Savolainen, Albert, Airavaara, & Myohanen, ). In addition, the observed motor deficits were not as prominent as in the original studies (Kordower et al., ; Manning‐Bog et al., ).…”
Section: Neurotoxin‐induced Modelsmentioning
confidence: 99%
“…The model produces α-synuclein protein expression in the dopaminergic neurons of the nigrostriatal tract which can cause loss of TH expression and unilateral motor deficits (Decressac et al, 2013;. While loss of TH in the SNpc is common in this model, the outcome of other measures often used in the field of animal models of PD such as loss of TH expression in the striatum, dopamine content levels, and certain motor phenotypes are less clearly observed or not shown at all (Albert et al, 2017).…”
Section: Adeno-associated Virus-alpha-synuclein Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteasomal dysfunction, leading to aberrant protein turnover and build-up of misfolded or damaged proteins, has emerged as a potential contributor to cell death in PD (Poewe et al, 2017 ) and might be linked to the accumulation of both non-ubiquitinated and ubiquitinated proteins in the SNpc and in Lewy bodies of PD patients (McNaught et al, 2001 ). Accordingly, administration of lactacystin (LAC), a selective proteasome inhibitor, leads to dopaminergic cell death when applied to the nigrostriatal pathway of rodents (Mackey et al, 2013 ; Savolainen et al, 2017 ). We recently reported that intranigral administration of LAC—reflecting PD pathology where proteasome dysfunction is limited to the SN (McNaught et al, 2003 )—leads to acute and non-progressive dopaminergic cell loss in mice (Bentea et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%